2008
DOI: 10.1017/s0022112007009433
|View full text |Cite
|
Sign up to set email alerts
|

Stability of flows past a pair of circular cylinders in a side-by-side arrangement

Abstract: The stability and transition of flow past a pair of circular cylinders in a side-by-side arrangement are investigated by numerical simulations and linear stability analyses. Various flow patterns around the cylinders have been reported to appear due to an instability of the steady symmetric flow that is realized at small Reynolds numbers, among which deflected oscillatory flow is particularly noticeable. The physical origin of the flow is explored by bifurcation analyses of the numerical data. We found that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
26
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(34 citation statements)
references
References 22 publications
5
26
1
Order By: Relevance
“…Many researchers suggested that the flow behind two side-by-side cylinders is mainly governed by the two non-dimensional parameters of Reynolds number (Re) and gap ratio, g* (g/D), where g is the spacing between 2 cylinders (Williamson, 1985;Kang, 2003;Mizushima and Ino, 2008;Carini et al, 2014). For square cylinders, the length of one edge is usually used as characteristic length D for both Re and g*.…”
Section: Introductionmentioning
confidence: 99%
“…Many researchers suggested that the flow behind two side-by-side cylinders is mainly governed by the two non-dimensional parameters of Reynolds number (Re) and gap ratio, g* (g/D), where g is the spacing between 2 cylinders (Williamson, 1985;Kang, 2003;Mizushima and Ino, 2008;Carini et al, 2014). For square cylinders, the length of one edge is usually used as characteristic length D for both Re and g*.…”
Section: Introductionmentioning
confidence: 99%
“…the symmetric base flow obtained by the Newton-Raphson method. For the employed parameters, in [12] was shown that two different global modes become linearly unstable: a steady, antisymmetric mode and an in-phase vortex shedding oscillatory mode. In our simulations, for Re = 68.8 and g = 0.7, the flow first evolves towards an oscillation analogous to the in-phase limit cycle.…”
Section: Dns Resultsmentioning
confidence: 99%
“…This hypothesis was supported by Mizushima and Ino [12], who computed the linear stability of the symmetric, steady base flow, because they found a narrow region in the parameter space where this flow bifurcates to an asymmetric steady solution.…”
mentioning
confidence: 75%
See 1 more Smart Citation
“…Of particular interest is to ascertain when the flow first becomes unstable and the mode of instability. Experiments, see for example Mizushima & Ino (2008), for the flow past two such cylinders show a complicated dynamics as the parameters are varied. For large Reynolds numbers, and for large gap widths the flow is like that past an isolated cylinder and the observed shedding frequencies also similar.…”
Section: Flow Past Circular Cylindersmentioning
confidence: 99%